Functional Alleles of Chicken BG Genes, Members of the Butyrophilin Gene Family, in Peripheral T Cells - Chen, Lei; Fakiola, Michaela; Staines, Karen; Butter, Colin; Kaufman, Jim (Frontiers in Immunology, 2018)
γδ T cells recognize a wide variety of ligands in mammals, among them members of the butyrophilin (BTN) family. Nothing is known about γδ T cell ligands in chickens, despite there being many such cells in blood and lymphoid tissues, as well as in mucosal surfaces. The major histocompatibility complex (MHC) of chickens was discovered because of polymorphic BG genes, part of the BTN family. All but two BG genes are located in the BG region, oriented head to tail so that unequal crossing over has led to copy number variation (CNV) as well as hybrid (chimeric) genes, making it difficult to identify true alleles. One approach is to examine BG genes expressed in particular cell types, which likely have the same functions in different BG haplotypes and thus can be considered “functional alleles”. We compared nearly full-length BG transcripts from peripheral T cells of four haplotypes (B2, B15, B19 and B21), and compared them to the BG genes of the B12 haplotype that previously were studied in detail. A dominantly-expressed BG gene was found in each haplotype, but with significant levels of subdominant transcripts in three haplotypes (B2, B15 and B19). Most sequences in three haplotypes (B15, B19 and B21) are closely related to BG8, BG9 and BG12 from the B12 haplotype. We found that variation in the extracellular immunoglobulin-variable-like (Ig-V) domain is mostly localized to the membrane distal loops but without evidence for selection. However, variation in the cytoplasmic tail composed of many amino acid heptad repeats does appear to be selected (although not obviously localized), consistent with an intriguing clustering of charged and polar residues in an apparent α-helical coiled-coil. In contrast, the dominantly-expressed BG gene in the B2 haplotype is identical to BG13 from the B12 haplotype, and most of the subdominant sequences are from the BG5-BG7-BG11 clade. Moreover, alternative splicing leading to intron read-through results in dramatically-truncated cytoplasmic tails, particularly for the dominantly-expressed BG gene of the B2 haplotype. The approach of examining “functional alleles” has yielded interesting data for closely related genes, but also thrown up unexpected findings for at least one haplotype.